Dimensions of Mentoring Among Female Managers – an Explanatory Factor Analysis Based on the Global Measure of Mentoring Practices - Klaudia Blachnicka (European Management Studies)
Purpose: The objective of the article is to identify the dimensions of mentoring experienced by female managers. The recognition of the mentoring dimensions serves a significant role in enhancing the understanding of the support received by the mentee and facilitating an accurate evaluation of mentoring within the managerial context, especially in the Polish socio-economic conditions. Design/methodology/approach: The paper presents the results of an exploratory factor analysis based on data, acquired through an online questionnaire, from 370 female managers at basic, middle and senior levels of management. 18 items Global Measure of Mentoring Practices were used to examine the extent of mentoring actions experienced by female managers. Findings: The study discovered that mentoring female managers can be analyzed in three dimensions. Psychosocial, cognitive and patronage mentoring were distinguished. All mentor activities indicated in the questionnaire were included and allocated to the relevant dimensions of mentoring. Practical implication: The study offers several recommendations based on the results of the research that address the diagnosis of mentoring, which is important in the process of evaluating the mentoring relationship and assessing its effectiveness. Originality/value: The current research provides novel insights about the mentoring relationship among managerial staff. The mentoring support received by managers can be analyzed in three dimensions, related to the various activities undertaken by the mentor.